Tribological and electrical behavior of Cu-based composites with addition of Ti-doped NbSe2 nanoplatelets. Issue 3 (9th April 2018) - Li, Jian Feng; Shi, Qin; Zhu, HeJun; Huang, ChenYu; Zhang, Shuai; Peng, Weixiang; Li, ChangSheng
Abstract : Purpose: This paper aims to clarify the size and morphology of transition metal dichalcogenides has an impact on lubrication performance of Cu-based composites. This study is intended to show that Cu-based electrical contact materials containing Nb0.91 Ti0.09Se2 have better electrical and tribological properties than those containing NbSe2 . The tribological properties of Cu-based with different Ti-dopped NbSe2 content were also discussed. Design/methodology/approach: The NbSe2 and Nb0.91 Ti0.09 Se2 particles were fabricated by thermal solid state reaction method. The powder metallurgy technique was used to fabricate composites with varying Nb0.91 Ti0.09 Se2 mass fraction. The phase composition of Cu-based composites was identified by X-ray diffraction, and the morphology of NbSe2 /Nb0.91 Ti0.09 Se2 and the worn surface of composites were characterized by scanning electron microscopy and transmission electron microscopy. In addition, the tribological properties of composites were appraised using a ball-on-disk multi-functional tribometer. The data of friction coefficient and resistivity were analyzed and the corresponding conclusion was drawn. Findings: In comparison with the pure copper, Cu-based composites containing Nb0.91 Ti0.09 Se2 /NbSe2 had a lower friction coefficient, illustrating the Nb0.91 Ti0.09 Se2 with nano-size particles prepared in this work is a perfect choice for the fabrication of excellent electrical contact composites. Compared to composites with NbSe2, composites containing Nb0.91 Ti0.09 Se2 have better tribological and electrical properties. Research limitations/implications: Because of the use of thermal solid state reaction method, the size of NbSe2 and Nb0.91 Ti0.09 Se2 is relatively large. Therefore, the fabrication of finer particles of Nb0.91 Ti0.09 Se2 is encouraged. Originality/value: In this paper, the authors discuss the tribological and electrical properties of Cu-based composites, and the value of optimum obtained as Nb0.91 Ti0.09 Se2 content is 15 Wt.%.